Autopercepção da condição bucal em diferentes grupos etários e seus fatores associados - Fagundes, Maria Laura Braccini (2020)
Oral health self-perception (OHSP) is a multidimensional measure which results from a complex web of factors including, in addition to individual characteristics, also the environment and context to which individuals are exposed. As it reflects the individuals’ experience regarding psychological, social and functional well-being, OHSP impacts quality of life. Therefore, to analyze the specific aspects that affect health at each stage of life can corroborate with health policies improvement, taking into account what is relevant for each age group. This study aimed to verify the factors associated with OHSP in adolescents, adults and older adults. This is a cross-sectional observational study with data from the São Paulo Oral Health Survey – 2015 (SBSP-2015), conducted in 163 municipalities, representative for the state of São Paulo. The sampling design comprised a cluster sampling in two-stages. Data from 5,314 adolescents (15-19 years), 5,815 adults (35-44) and 5,556 older adults (65+) were analyzed. The outcome was assessed by a global self-rating item. Variables regarding demographic and socioeconomic factors, social capital and dental attendance were collected, in addition to clinical variables, including number of decayed and missing teeth, dental prosthesis use and dental prosthesis need. Hierarchical Poisson regression models were performed, using the svy command, to estimate prevalence ratios (PR) and its confidence intervals (95%CI). Analyzes for each age group were performed separately and then compared. Female adolescents and adults, as well as non-white adults and older adults with a higher educational level had worse OHSP. Having lower social capital increased the prevalence of negative OHSP in adolescents, adults and older adults by 56%, 28% and 21%, respectively. Individuals whose reason for last dental attendance was treatment had a higher prevalence of the outcome for the three age groups. In the final model, adolescents, adults and older adults with greater amount of decayed teeth showed 56%, 30% and 29% higher prevalence of negative OHSP, respectively. Adolescents and adults with higher number of missing teeth showed, respectively, 23% and 9% higher prevalence negative OHSP. The older adults with dental prosthesis need showed two times higher prevalence of negative OHSP. Therefore, there are differences among the factors associated with negative OHSP in different age groups. Intergenerational aspects seem to play a role on the way individuals perceive their oral health. In addition, this study findings reinforce the relevance of planning and evaluating health actions and policies considering the life cycles.